Long-acting water-resistant glass cement, preparation method thereof and application of long-acting water-resistant glass cement in aquarium fish tank
By dispersing the aging-resistant filler of modified white carbon black and modified silicon carbide nanowires in glass glue, the problems of aging and leakage of traditional glass glue in aquarium fish tanks are solved, achieving higher water resistance and mechanical strength, and extending service life.
Patent Information
- Application Number
- CN202411552964.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-11
AI Technical Summary
Traditional glass glue is prone to aging, cracking and leaking when used in aquarium fish tanks for a long time, resulting in a decrease in the quality and service life of the fish tank.
Aging-resistant fillers including modified white carbon black and modified silicon carbide nanowires are used to disperse these fillers in the glass glue matrix to form a filling framework, reduce moisture penetration channels, and increase the mechanical strength of the glass glue.
It significantly extends the service life of glass glue and water aging resistance, and can maintain a good sealing effect in high water pressure and complex environments.
Smart Images

Figure BDA0005115560420000111 
Figure BDA0005115560420000121
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of glass glue, and in particular to a long-lasting water-resistant glass glue and a preparation method thereof and application thereof in an aquarium fish tank. Background Art
[0002] As people's pursuit of quality of life continues to improve, aquariums and home fish tanks are becoming more and more popular. In the construction process of fish tanks in aquariums, glass glue can be used as an adhesive to bond and seal high-strength glass. Its performance directly affects the quality and service life of the fish tank. However, traditional glass glue has many shortcomings in water resistance and durability. During long-term and high-pressure use, glass glue is prone to aging, cracking and leakage. Therefore, it is urgent to provide a solution to improve the above problems. Summary of the invention
[0003] The invention aims to provide a long-lasting water-resistant glass glue and a preparation method thereof and application thereof in an aquarium fish tank.
[0004] In a first aspect, the present invention provides a long-lasting water-resistant glass glue, comprising a glass glue matrix and an aging-resistant filler dispersed in the glass glue matrix, wherein the aging-resistant filler comprises a composition of modified silica and modified silicon carbide nanowires; a method for preparing the modified silica comprises: stirring and mixing the silica in cashew nut shell oil, separating, washing and drying the mixture to obtain the modified silica; and a method for preparing the modified silicon carbide nanowires comprises: modifying the surface of the surface-activated silicon carbide nanowires with melamine to obtain the modified silicon carbide nanowires.
[0005] Optionally, the mass ratio of the modified white carbon black to the modified silicon carbide nanowires in the aging-resistant filler is 1:(0.8-1.2).
[0006] Optionally, the particle size of the anti-aging filler is 1-50 μm.
[0007] Optionally, the mass fraction of the anti-aging filler in the glass glue matrix is 1-3%.
[0008] Optionally, the method for preparing the aging-resistant filler comprises: ultrasonically dispersing modified white carbon black and modified silicon carbide nanowires in deionized water to obtain a mixed suspension, and then spray-drying the mixed suspension to obtain the aging-resistant filler.
[0009] Optionally, the preparation method of the modified silica comprises the following steps: ultrasonically mixing silica in an alkaline solution and then separating to obtain a modified precursor; stirring and mixing the modified precursor in cashew nut shell oil and performing high-energy ball milling, centrifugally separating, washing and drying to obtain the modified silica.
[0010] Optionally, the solute in the alkaline solution includes one of sodium hydroxide and potassium hydroxide.
[0011] Optionally, the pH of the alkaline solution is 12-14.
[0012] Alternatively, the silica is mixed in an alkaline solution by ultrasound at a frequency of 10-20 kHz.
[0013] Alternatively, the modified precursor is stirred and mixed in cashew nut shell liquid at 40-50°C.
[0014] Optionally, the solid-liquid ratio of the modified precursor to the cashew nut shell liquid is 1:(5-6).
[0015] Optionally, the modified precursor is mixed with cashew nut shell liquid, and then ball milled for 8-10 hours at a ball-to-material ratio of (10-15):1 and a ball milling speed of 200 rpm.
[0016] Optionally, the method for preparing the modified silicon carbide nanowires comprises the following steps: stirring and mixing the silicon carbide nanowires in a silane active solution, separating and drying to obtain activated nanowires, stirring and reacting the activated nanowires with melamine in an alkyd solution, and separating and drying to obtain modified silicon carbide nanowires.
[0017] Optionally, the solute in the silane active solution includes one of KH-550, KH-792, KH-560, and KH-580.
[0018] Optionally, the solid-to-liquid ratio of the silicon carbide nanowires to the silane active solution is 0.05-0.08 g / mL.
[0019] Alternatively, the silicon carbide nanowires are ultrasonically mixed in a silane reactive solution at 45-50°C.
[0020] Optionally, the mass ratio of the activated nanowires to the melamine is 1:(0.2-0.3).
[0021] Optionally, the alkyd solution is formic acid and methanol in a volume ratio of 1:1.
[0022] Optionally, the glass glue matrix includes silicone rubber, a cross-linking agent, a reinforcing filler, a plasticizer, a catalyst and a functional additive; and in parts by mass, the glass glue includes 60-70 parts of silicone rubber, 1-3 parts of a cross-linking agent, 15-20 parts of a reinforcing filler, 1-3 parts of a plasticizer, 0.5-0.8 parts of a catalyst, 1-5 parts of a functional additive and 1-5 parts of an aging-resistant filler.
[0023] Optionally, the silicone rubber includes one of vinyl polysiloxane, vinyl-terminated polydimethylsiloxane and polydimethylsiloxane.
[0024] Optionally, the crosslinking agent includes one of methyltrimethoxysilane and vinyltrimethoxysilane.
[0025] Optionally, the reinforcing filler includes one of fumed silica and calcium carbonate nanopowder.
[0026] Optionally, the plasticizer includes one of dioctyl phthalate and tricresyl phosphate.
[0027] Optionally, the catalyst includes one of dibutyltin dilaurate and stannous octoate.
[0028] Optionally, the functional additives include dyes, mildew preventers and UV inhibitors.
[0029] In a second aspect, the present invention further provides a method for preparing any of the above-mentioned optional glass glues, comprising: stirring, mixing and grinding a glass glue matrix and an aging-resistant filler, and then vacuum degassing to obtain the glass glue.
[0030] In a third aspect, the present invention further provides a use of glass glue prepared by any of the above-mentioned optional glass glue preparation methods in an aquarium fish tank. DETAILED DESCRIPTION
[0031] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Unless otherwise defined, the technical terms or scientific terms used herein should be the common meanings understood by people with general skills in the field to which the present invention belongs.
[0032] The present invention provides a long-lasting water-resistant glass glue, comprising a glass glue matrix and an anti-aging filler dispersed in the glass glue matrix. In fact, after the glass glue matrix is cured, it has good water resistance. However, when it is in contact with water for a long time and in a high water pressure environment in the fish tank of an aquarium, the simple glass glue matrix is easily penetrated by water and loses its viscosity, thereby causing water leakage or other situations. Therefore, adding the anti-aging filler therein can fill the tiny pores inside the glass glue and form a filling skeleton, thereby reducing the water penetration channel and improving the mechanical strength of the glass glue, thereby effectively extending the service life and water-resistant aging performance of the glass glue.
[0033] Specifically, the aging-resistant filler includes a composition of modified silica and modified silicon carbide nanowires. In fact, silica itself has high chemical stability. After surface modification of silica, the compatibility of silica in the glass glue matrix can be effectively improved, and the modified silica and modified silicon carbide nanowires can be connected to form a stable filling skeleton.
[0034] In addition, the modified silica and modified silicon carbide nanowires in the aging-resistant filler can not only play a filling role, but also improve their own adhesion to the glass glue matrix, thereby further improving the compatibility of the aging-resistant filler in the glass glue matrix, and at the same time improve the mechanical strength of the glass glue, so that the glass glue can be suitable for sealing scenarios of fish tank glass with greater water pressure.
[0035] In fact, by using modified silica and modified silicon carbide nanowires in aging-resistant fillers, the water resistance of glass glue can be more effectively improved, and the fluctuations caused by the impact of water flow under high water pressure can be reduced, thereby maintaining the structural integrity of the glass glue itself, so that the glass glue can maintain good performance for a long time in the complex and harsh environment of an aquarium fish tank.
[0036] In some embodiments, the mass ratio of modified silica to modified silicon carbide nanowires in the aging-resistant filler is 1:(0.8-1.2). In fact, by adjusting the mixing ratio of modified silica to modified silicon carbide nanowires, the synergistic effect of modified silica and modified silicon carbide nanowires can be adjusted. When the amount of modified silicon carbide nanowires is too much, the toughness of the glass glue will be too high, thereby inhibiting the water resistance of the glass glue. When the amount of modified silica is too much, it will affect the mechanical strength and water pressure resistance of the glass glue, making it difficult to resist the water pressure changes and water shock in the fish tank environment.
[0037] In some embodiments, the particle size of the aging-resistant filler is 1-50 μm, and in fact, the average particle size of the aging-resistant filler can be 20-30 μm. In fact, the use of aging-resistant fillers with small particle sizes can effectively increase the specific surface area, thereby improving the compatibility of the aging-resistant fillers in the glass glue matrix, and can also play a good filling role in the pores in the glass glue after curing, thereby improving the density of the glass glue. At the same time, the aging-resistant fillers within this particle size range can be more evenly dispersed in the glass glue matrix, thereby forming a uniform glue.
[0038] In some embodiments, the mass fraction of the aging-resistant filler in the glass glue matrix is 1-3%, which can effectively improve the dispersibility of the aging-resistant filler in the glass glue matrix and balance the viscosity, fluidity and water aging resistance of the glass glue. In fact, when too much aging-resistant filler is added to the glass glue matrix and solidified, the excess aging-resistant filler will form a denser filling structure, which greatly reduces the viscosity of the glass glue.
[0039] In some embodiments, when preparing the anti-aging filler, the method includes: ultrasonically dispersing the modified silica and the modified silicon carbide nanowires in deionized water to obtain a mixed suspension, and then spray-drying the mixed suspension to obtain the anti-aging filler. In fact, ultrasonically dispersing the modified silica and the modified silicon carbide nanowires can effectively promote the uniform dispersion of the modified silica and the modified silicon carbide nanowires, and avoid agglomeration and sedimentation of the two. At the same time, after spray drying, the particles of the anti-aging filler can be made more uniform and maintain a good dispersion effect.
[0040] Specifically, the modified silica and the modified silicon carbide are mixed in deionized water at a solid-liquid ratio of 10-20 g / L for ultrasonic mixing, and the mixed suspension is spray-dried using a spray dryer. In fact, the air inlet temperature of the spray dryer is 160-180°C.
[0041] Specifically, the preparation method of modified silica includes: stirring and mixing silica in cashew nut shell oil, separating, washing and drying to obtain modified silica. In fact, cashew nut shell oil contains a variety of organic components such as phenolic compounds. When cashew nut shell oil is mixed with silica, the effective ingredients in the cashew nut shell oil can chemically react and physically adsorb with the surface of silica, thereby forming a uniform cashew shell modified layer on the surface of silica. In this way, when the modified silica is dispersed in the glass glue matrix and cured, the cashew shell modified layer on the surface of silica can react with the glass glue matrix, thereby improving compatibility.
[0042] In fact, the hydrophilicity of silica can be improved by using cashew nut shell oil to modify the surface of silica. After the cashew nut shell modified layer coats the silica, the surface of the modified silica becomes hydrophobic. When the modified silica is added to the glass glue matrix, part of the modified silica will solidify on the surface of the glass glue after curing, thereby reducing the hydrophilicity of the glass glue surface.
[0043] In some embodiments, the method for preparing modified silica comprises the following steps:
[0044] S1, mixing white carbon black in an alkaline solution by ultrasonication and then separating to obtain a modified precursor;
[0045] S2, stirring and mixing the modified precursor in cashew nut shell liquid and performing high-energy ball milling to obtain a modified intermediate;
[0046] S3, centrifugally separating the modified intermediate, washing and drying the modified silica.
[0047] In fact, ultrasonic mixing of silica with alkaline solution can modify the surface of silica with hydroxyl groups and promote the activation of hydroxyl groups on the surface of silica. The cavitation effect during ultrasonic mixing can effectively avoid the agglomeration and sedimentation of silica in the alkaline solution, promote the contact reaction between the alkaline solution and the surface of silica, and increase the active sites on the surface of silica.
[0048] In addition, after the modified precursor and cashew nut shell liquid are mixed, high-energy ball milling is performed. Since the modified precursor and cashew nut shell liquid are in more complete contact during the ball milling process, and the strong mechanical force can break through the mass transfer limitation in the reaction process, the organic components in the cashew nut shell liquid can undergo modification reaction with the active sites on the surface of the modified precursor faster and more deeply, thereby forming a uniform cashew nut shell oil modified layer, which can further strengthen the modification reaction between the cashew nut shell oil and the surface of the modified precursor.
[0049] In fact, by centrifugal separation, the modified precursor whose surface is modified with cashew nut shell oil can be completely separated from the cashew nut shell oil, avoiding excessive cashew nut shell oil from being mixed in the pores on the surface of the modified precursor, thereby affecting the compatibility of the modified silica. In addition, washing and drying can ensure the purity of the surface of the modified silica, reduce the impurity components on the surface of the modified silica, and facilitate the dispersion of the modified silica in the glass glue matrix.
[0050] In some embodiments, the solute of the alkaline solution used in step S1 includes one of sodium hydroxide and potassium hydroxide, and the solute of the alkaline solution can be deionized water. In fact, the alkaline solution is necessary to be able to perform uniform hydroxyl modification treatment on the surface of silica. Specifically, the pH of the alkaline solution can be 12-14. By using an alkaline solution with strong alkalinity, the number of active hydroxyl groups on the surface of silica can be effectively increased, thereby improving the reaction activity of the surface of silica.
[0051] In some embodiments, when executing step S1, after adding silica to the alkaline solution, ultrasound with a frequency of 10-20 kHz is applied for ultrasonic mixing treatment, which can effectively utilize the ultrasonic cavitation effect to evenly disperse the silica agglomerated and precipitated in the alkaline solution, so that the alkaline solution can evenly and consistently modify the silica.
[0052] In some embodiments, when performing step S2, the modified precursor is stirred and mixed in cashew nut shell liquid at 40-50° C., which is conducive to improving the reactivity of cashew nut shell liquid, thereby promoting the organic components in the cashew nut shell liquid to react with the hydroxyl groups on the surface of the modified precursor. In fact, when the temperature is too low, the reaction rate of cashew nut shell liquid with the surface of the modified precursor will be significantly inhibited, thereby affecting the modification effect of cashew nut shell liquid on the modified precursor, and when the temperature is too high, more energy is required, which is not conducive to reducing the reaction cost.
[0053] In some embodiments, when performing step S2, the solid-liquid mixing ratio of the modified precursor to the cashew nut shell liquid is 1: (5-6). This is conducive to the uniform dispersion of the modified precursor in the cashew nut shell liquid, and at the same time, the modified precursor can be maintained within a certain density range after being dispersed in the cashew nut shell liquid to ensure the modification effect of the cashew nut shell liquid on the modified precursor. In addition, when performing step S2, after the modified precursor is mixed with the cashew nut shell liquid, it is ball milled for 8-10h at a ball-to-material ratio of (10-15): 1 and a ball milling speed of 200rpm.
[0054] Specifically, the preparation of modified silicon carbide nanowires includes: modifying the surface of silicon carbide nanowires with melamine after surface activation to obtain modified silicon carbide nanowires. In fact, after the silicon carbide nanowires are pre-activated, surface active sites of the silicon carbide nanowires can be effectively added, and the wettability of the silicon carbide nanowires can be improved, which is conducive to the combination of silicon carbide nanowires and melamine, so that melamine can be spread in situ on the surface of the silicon carbide nanowires.
[0055] In addition, by modifying the surface of silicon carbide nanowires with melamine, the hydrophobicity of the silicon carbide nanowires can be improved, so that after curing into the glass glue, the surface hydrophobicity of the glass glue can be improved to a certain extent. At the same time, melamine can be well cross-linked with the long-chain organic matter in the glass glue matrix, thereby improving the compatibility of the modified silicon carbide nanowires.
[0056] In some embodiments, the method for preparing modified silicon carbide nanowires comprises the following steps:
[0057] Y1. Stirring and mixing silicon carbide nanowires in a silane active solution, and then separating and drying to obtain activated nanowires;
[0058] Y2. After the activated nanowires and melamine are stirred and reacted in an alkyd solution, the mixture is separated and dried to obtain modified silicon carbide nanowires.
[0059] In fact, when executing step Y1, after the silicon carbide nanowires are surface-treated with a silane active solution, the silane groups in the silane active solution can undergo a condensation reaction with the hydroxyl groups on the surface of the silicon carbide nanowires, thereby introducing silane groups on the surface of the silicon carbide nanowires, thereby effectively changing the surface activity of the silicon carbide nanowires, which is beneficial to the subsequent loading of melamine.
[0060] In some embodiments, when performing step Y1, the solute in the silane active solution used includes one of KH-550, KH-792, KH-560, and KH-580, and the solvent of the silane active solution can be an organic solvent commonly used in the art, which is necessary to be able to dissolve one of KH-550, KH-792, KH-560, and KH-580.
[0061] In some embodiments, when performing step Y1, the solid-liquid ratio of silicon carbide nanowires to the silane active solution is 0.05-0.08 g / mL, and the mass ratio of silicon carbide nanowires to the solute in the silane active solution is 1:(0.1-0.2). This is conducive to the uniform dispersion of silicon carbide nanowires in the silane active solution and promotes the silane solute in the silane active solution to uniformly modify the silicon carbide nanowires.
[0062] In fact, when performing step Y1, the silicon carbide nanowires are preheated at 45-50°C for 30-60 minutes, and then the preheated silicon carbide nanowires are added to the silane active solution in a 45-50°C water bath for ultrasonic mixing. This is conducive to improving the activity and reaction rate of silane modification on the surface of the silicon carbide nanowires.
[0063] Specifically, when performing step Y2, the alkyd solution provides a suitable reaction medium for the reaction between the active nanowires and melamine, which can completely dissolve the melamine and evenly disperse it, which is beneficial to improve the uniformity of melamine on the surface of the active nanowires. At the same time, the mass ratio of the activated nanowires to melamine is 1: (0.2-0.3), and the alkyd solution is formic acid and methanol in a volume ratio of 1: 1.
[0064] In fact, the glass glue matrix includes silicone rubber, cross-linking agent, reinforcing filler, plasticizer, catalyst and functional additive. In addition, the long-lasting water-resistant glass glue provided by the present invention includes 60-70 parts of silicone rubber, 1-3 parts of cross-linking agent, 15-20 parts of reinforcing filler, 1-3 parts of plasticizer, 0.5-0.8 parts of catalyst, 1-5 parts of functional additive and 1-5 parts of anti-aging filler by weight.
[0065] Specifically, the silicone rubber includes one of vinyl polysiloxane, terminal vinyl polydimethylsiloxane, and polydimethylsiloxane; the cross-linking agent includes one of methyl trimethoxy silane and vinyl trimethoxy silane; the reinforcing filler includes one of fumed silica and calcium carbonate nanopowder; the plasticizer includes one of dioctyl phthalate and tricresyl phosphate; the catalyst includes one of dibutyl tin dilaurate and stannous octoate; the functional additives include a dye, a mildew inhibitor, and an anti-ultraviolet agent.
[0066] The present invention also provides a method for preparing a long-lasting water-resistant glass glue, comprising: stirring, mixing and grinding a glass glue matrix and an aging-resistant filler, and then vacuum degassing to obtain the glass glue. In addition, the glass glue provided by the present invention can be used in aquarium fish tanks, and has good water aging resistance and water impact resistance.
[0067] Preparation Example 1
[0068] This preparation example 1 provides a method for preparing modified white carbon black, comprising the following steps:
[0069] S1. The white carbon black was subjected to ultrasonic treatment at a frequency of 10 kHz for 10 min in a sodium hydroxide solution having a pH of 14, and then separated by filtration under reduced pressure, and then dried in a hot air drying oven at 45° C. to a constant weight to obtain a modified precursor;
[0070] S2, after the modified precursor and cashew nut shell liquid are mixed at a solid-liquid ratio of 1:6, the ball-to-material ratio is 10:1 in a ball mill, and zirconium oxide is used as a ball milling ball, and the ball milling treatment is carried out at a speed of 200 rpm for 10 hours to obtain a modified intermediate;
[0071] S3. The modified intermediate is centrifuged at 500 rpm in a centrifugal device to separate the precipitate, and the precipitate is cyclically rinsed with anhydrous ethanol and deionized water, and then dried in a hot air drying oven at 45° C. to constant weight to obtain modified silica.
[0072] Preparation Example 2
[0073] This preparation example 2 provides a method for preparing modified white carbon black, comprising the following steps:
[0074] S1. The white carbon black was ultrasonically treated in a sodium hydroxide solution with a pH of 14 at a frequency of 10 kHz for 10 min, and then separated by vacuum filtration, and then dried in a hot air drying oven at 45° C. to constant weight to obtain modified white carbon black.
[0075] Preparation Example 3
[0076] This preparation example 3 provides a method for preparing modified white carbon black, comprising the following steps:
[0077] S1. Mix white carbon black and cashew nut shell oil at a solid-liquid ratio of 1:6, and then use zirconium oxide as ball milling balls in a ball mill at a ball-to-material ratio of 10:1 for 10 hours at a rotation speed of 200 rpm to obtain a modified intermediate;
[0078] S2. The modified intermediate is centrifuged at 500 rpm in a centrifugal device to separate the precipitate, and the precipitate is cyclically rinsed with anhydrous ethanol and deionized water, and then dried in a hot air drying oven at 45° C. to constant weight to obtain modified silica.
[0079] Preparation Example 4
[0080] This preparation example 4 provides a method for preparing modified silicon carbide nanowires, comprising the following steps:
[0081] Y1. After ultrasonically mixing silicon carbide nanowires in a KH550 ethanol solution (the mass ratio of silicon carbide nanowires to KH550 is 1:0.2), centrifugation is performed and the mixture is dried in a 50°C hot air drying oven to a constant weight to obtain activated nanowires;
[0082] Y2. The activated nanowires and melamine were mixed in a mass ratio of 1:0.2 and put into an alkyd solution (formic acid and methanol in a volume ratio of 1:1) and stirred for reaction. The mixture was separated by vacuum filtration and rinsed with anhydrous ethanol. The mixture was dried in a hot air drying oven at 50°C to constant weight to obtain modified silicon carbide nanowires.
[0083] Preparation Example 5
[0084] This preparation example 5 provides a method for preparing modified silicon carbide nanowires, comprising the following steps:
[0085] Y1. Silicon carbide nanowires and melamine were mixed in a mass ratio of 1:0.2 and put into an alkyd solution (formic acid and methanol in a volume ratio of 1:1) for stirring and reacting. The mixture was separated by vacuum filtration and rinsed with anhydrous ethanol. The mixture was dried in a hot air drying oven at 50°C to constant weight to obtain modified silicon carbide nanowires.
[0086] Preparation Example 1 to Preparation Example 9
[0087] Preparation Examples 1 to 9 provide a method for preparing an aging-resistant filler, respectively, comprising: mixing modified white carbon black and modified silicon carbide at a mass ratio of 1:1, adding the mixture into deionized water at a solid-liquid ratio of 15 g / L for ultrasonic mixing to obtain a mixed suspension, and spray drying the mixed suspension at an air inlet temperature of 170° C. using a spray dryer to obtain an aging-resistant filler. The modified white carbon black and modified silicon carbide nanowires used are specifically shown in Table 1 below, and pure white carbon black is used as Blank Example 1, and pure silicon carbide nanowires are used as Blank Example 2.
[0088] Table 1 Aging-resistant fillers in Preparation Examples 1 to 6
[0089]
[0090]
[0091] Example 1 to Example 12
[0092] The present embodiments 1 to 12 provide a long-lasting water-resistant glass glue, wherein the glass glue matrix comprises 65 parts of vinyl polysiloxane, 2 parts of methyltrimethoxysilane, 17 parts of fumed silica, 2 parts of dioctyl phthalate, 0.5 parts of dibutyltin dilaurate and 3 parts of anti-aging filler. The anti-aging fillers in embodiments 1 to 12 are respectively Preparation Examples 1 to 12.
[0093] Performance Testing
[0094] The glass glue prepared in Examples 1 to 12 was used to seal five square glasses with a size of 1 m, and formed into a fish tank structure with an opening on the top. After the structure was filled with water, an accelerated heat aging test was performed at 60° C. It was observed whether water leakage occurred during the test, and the adhesion of the glass glue to the glass was detected before and after the test, and the adhesion attenuation rate was calculated as shown in Table 2 below;
[0095] The glass glue prepared in Examples 1 to 12 was used to seal five square glasses with a size of 10 cm, and a structure with an opening on the top was formed. 5 atm of water vapor was injected into the structure, and the top was sealed and kept warm. It was observed whether there was leakage after 48 hours, as shown in Table 2 below.
[0096] Table 2 Performance test results
[0097] Is there any water leakage? Adhesion attenuation rate / % Is there any leakage? Example 1 no 0.1 no Example 2 no 0.8 no Example 3 no 1.5 no Example 4 no 0.4 no Example 5 no 1.1 no Example 6 no 2.5 Air leak Example 7 no 0.3 no Example 8 no 0.9 no Example 9 no 1.2 no Example 10 no 0.7 no Embodiment 11 no 1.6 no Example 12 no 3.5 Air leak
[0098] As can be seen from Tables 1 and 2, the glass glue provided by the present invention can be used well in a high temperature and high pressure water environment, especially in the aquarium fish tank sealing application, it can improve the long-term water resistance and aging resistance. As can be seen from Example 1, when the modified white carbon black and the modified silicon carbide nanowires are used in combination, the bonding strength of the glass glue can be comprehensively improved. At the same time, because it can fill the tiny pores of the glass glue and form a filling structure, it can play a long-term water resistance, and can still play a good sealing effect in a high temperature and high pressure water vapor environment. As can be seen from Example 2, when the surface of the modified silicon carbide nanowire is not loaded with a cashew nut shell oil modified layer, it will significantly affect the bonding stability of the glass glue, resulting in a decrease in its bonding strength.
[0099] Although the embodiments of the present invention are described in detail above, it is obvious to those skilled in the art that various modifications and variations can be made to these embodiments. However, it should be understood that such modifications and variations are within the scope and spirit of the present invention as described in the claims. Moreover, the present invention described herein may have other embodiments and may be implemented or realized in a variety of ways.
Claims
1. A long-lasting water-resistant glass adhesive, characterized in that: It comprises a glass glue matrix and an anti-aging filler dispersed in the glass glue matrix, wherein the anti-aging filler comprises a composition of modified white carbon black and modified silicon carbide nanowires; The preparation of the modified white carbon black comprises: mixing white carbon black in cashew nut shell oil, separating, washing and drying to obtain the modified white carbon black; the preparation of the modified silicon carbide nanowire comprises: modifying the surface of the surface activated silicon carbide nanowire with melamine to obtain the modified silicon carbide nanowire.
2. The glass glue according to claim 1, characterized in that: The mass ratio of the modified white carbon black to the modified silicon carbide nanowires in the anti-aging filler is 1:(0.8-1.2); and / or the particle size of the anti-aging filler is 1-50 μm; And / or, the mass fraction of the aging-resistant filler in the glass glue matrix is 1-3%; and / or, the preparation method of the aging-resistant filler comprises: ultrasonically dispersing modified silica and modified silicon carbide nanowires in deionized water to obtain a mixed suspension, and then spray-drying the mixed suspension to obtain the aging-resistant filler.
3. The glass glue according to claim 1, characterized in that: The preparation method of modified white carbon black comprises the following steps: ultrasonically mixing white carbon black in an alkaline solution and then separating to obtain a modified precursor; stirring and mixing the modified precursor in cashew nut shell oil and performing high-energy ball milling, centrifugally separating, washing and drying to obtain the modified white carbon black.
4. The glass glue according to claim 3, characterized in that: The solute in the alkaline solution includes one of sodium hydroxide and potassium hydroxide; and / or the pH of the alkaline solution is 12-14; and / or the white carbon black is ultrasonically mixed in the alkaline solution at a frequency of 10-20kHz; and / or the modified precursor is stirred and mixed in cashew nut shell oil at 40-50°C; and / or the solid-liquid ratio of the modified precursor to the cashew nut shell oil is 1:(5-6); and / or, after the modified precursor is mixed with the cashew nut shell oil, it is ball milled for 8-10h at a ball-to-material ratio of (10-15):1 and a ball milling speed of 200rpm.
5. The glass glue according to claim 1, characterized in that: The preparation method of the modified silicon carbide nanowires comprises the following steps: stirring and mixing the silicon carbide nanowires in a silane active solution, separating and drying to obtain activated nanowires, stirring and reacting the activated nanowires with melamine in an alkyd solution, and separating and drying to obtain modified silicon carbide nanowires.
6. The glass glue according to claim 5, characterized in that: The solute in the silane active solution includes one of KH-550, KH-792, KH-560, and KH-580; and / or, the solid-liquid ratio of the silicon carbide nanowires to the silane active solution is 0.05-0.08 g / mL; and / or, the silicon carbide nanowires are ultrasonically mixed in the silane active solution at 45-50° C.; and / or, the mass ratio of the activated nanowires to the melamine is 1:(0.2-0.3); and / or, the alkyd solution is formic acid and methanol in a volume ratio of 1:
1.
7. The glass glue according to claim 1, characterized in that: The glass glue matrix includes silicone rubber, a cross-linking agent, a reinforcing filler, a plasticizer, a catalyst and a functional additive; and in parts by mass, the glass glue includes 60-70 parts of silicone rubber, 1-3 parts of a cross-linking agent, 15-20 parts of a reinforcing filler, 1-3 parts of a plasticizer, 0.5-0.8 parts of a catalyst, 1-5 parts of a functional additive and 1-5 parts of an anti-aging filler.
8. The glass glue according to claim 1, characterized in that: The silicone rubber includes one of vinyl polysiloxane, vinyl-terminated polydimethylsiloxane, and polydimethylsiloxane; and / or, the cross-linking agent includes one of methyltrimethoxysilane and vinyltrimethoxysilane; and / or, the reinforcing filler includes one of fumed silica and calcium carbonate nanopowder; and / or, the plasticizer includes one of dioctyl phthalate and tricresyl phosphate; and / or, the catalyst includes one of dibutyltin dilaurate and stannous octoate; and / or, the functional additive includes a colorant, a mildew inhibitor, and an anti-ultraviolet agent.
9. A method for preparing glass glue according to any one of claims 1 to 8, characterized in that: include: The glass glue matrix and the anti-aging filler are stirred, mixed and ground, and then vacuum degassing is performed to obtain the glass glue.
10. Use of the glass glue according to any one of claims 1 to 8 or the glass glue prepared by the preparation method according to claim 9 in an aquarium fish tank.